Current Legal Issues Affecting Central Banks, Volume II. - Effros, Robert (International Monetary Fund, 1994)
Volume II, edited by Robert C. Effros, contains the collected views of banking and legal experts, gathered at the second IMF-sponsored seminar of central banks general counsels. Matters of both international and domestic concern are addressed. The contributors analyze topics ranging from concepts of international monetary law to aspects of the debt crisis and the role of the international financial institutions; banking development in the United States, the United Kingdom, the European Union, and elsewhere; developments in the payments systems; and measures to counter money laundering.